Water absorption of lignocellulosic phenolic composites - Lai, J.C.; Ani, F.N.; Hassan, A. (RAPRA Technology Ltd, 2008)
The main objective of this study is to investigate the effect of filler content and filler size on the water absorption behaviour of phenolic composites filled with oil palm shell flour, rice husk flour and coconut shell flour. Lignocellulosic phenolic composites with three different filler sizes (<38 Î¼m, 38-75 Î¼m and 75-150 Î¼m) and at three different filler loadings (30%, 45% and 55%) were prepared using a two-roll mill before being hot pressed. A pure Novolak sample was produced via the same method. The water absorption rate at different times, the diffusion coefficients, and the kinetic parameters k and n of the samples were calculated. All the samples exhibited a Fickian diffusion mechanism The water absorption rate and the quantity of water absorbed by the composites increased noticeably with increasing filler loading due to the hydrophilic nature of the lignocellulosic fillers. However, filler size does not significantly influence these properties.